Narratives on the Inclusion of Autistic Students: Challenges and Teaching Practices - Mariana Helena Silva Da Luz; Candido Alberto Gomes; Adriana Lira (Pontificia Universidad Católica del Perú, 2017)
Autism is a widely explored theme in the literature. Nevertheless, school inclusion among autistic children still constitutes a challenge. On this basis, the general goal of this research was to identify the challenges of teaching practices in the monitoring of an autistic student and in which conditions his inclusion occurs. The qualitative research, descriptive and exploratory in its nature, is characterized as a case study that was conducted in the months of August to October 2014 in a private institution of Brasilia. In summary, the study, by means of semi-structured interviews and on-site observations, concluded that the school»s inclusion proposal, in which parents seem to trust, is weakened by the lack of professional preparation, a fact derived by the precariousness of initial and continuous training of these professionals.